Impact evaluation of Netherlands supported programmes in the area of energy and development cooperation in Rwanda: The provision of grid electricity to households through the Electricity Access Roll-out Programme. Electricity Access Roll-out Programme (EARP) supported by the Netherlands through a multi-donor fund - Jörg Peters; Maximiliane Sievert; Luciane Lenz; Anicet Munyehirwe (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
This report is part of an evaluation commissioned by the Policy and Operations Evaluation Department (IOB) of the Netherlands Ministry of Foreign Affairs. It belongs to a series of impact evaluations of renewable energy and development programmes supported by the Netherlands, with a focus on the medium and long-term effects of these programmes on end-users or final beneficiaries. A characteristic of these studies is the use of mixed methods, that is, quantitative research techniques in combination with qualitative techniques. The purpose of the impact evaluations is to account for assistance provided and to draw lessons from the findings for improvement of policy and policy implementation. The results of these impact evaluations will serve as inputs to a policy evaluation of the "Promoting Renewable Energy Programme" (PREP) to be concluded in 2014.
Keywords: 330